Date Fiber as a Constituent of Broiler Starter Diets - W. AI-Marzooki; A. AI-Halhali; R. AI-Maqbaly; A. Ritchie; K. Annamalai; N.E. Forsberg (Journal of Agricultural and Marine Sciences, 2000)
In Oman, efforts are underway to find alternative sources of fwd to support domestic livestock. The date industry thrives in Oman and one of its by-products is date fiber, a by-product of date syrup production. Although the product contains some free sugars, an evaluation of its potential in broiler diets has never been undertaken. Therefore, we conducted an experiment to investigate the value of date fiber in broiler chick diets. The experimental diets consisted of four graded levels of date fiber: 0, 15, 30 and 45 % in a broiler-starter ration replacing corn as an energy source. The diets were isonitrogenous. There were five replicates for each of the four diets and each replicate contained six broiler chicks. As date fiber percent increased in the dietary treatment, there were linear reductions in body weight gain, calculated apparent metabolizable energy (AMEn) content, and apparent protein digestibility (P < 0.05). Poor feed utilization (i .e., reduced feed efficiency) was observed in birds fed date fiber diets compared to the control group (P < 0.05). The poor performance of birds fed date fiber may be attributed to protein and energy limitations. We conclude that date fiber has no value in growing broiler diets. However, it may have utility in diets where a stable body weight is desirable.